Il contributo dell’Avvocato ai fini del Processus brevior (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. Il contributo in generale dell’Avvocato al processo matrimoniale - 3. Il ruolo dell’Avvocato nella fase pregiudiziale - 4. Il libello quale cardine del Processus brevior - 5. Il ridimensionamento del ruolo del DV nel Processus brevior - 6. La centralità del ruolo dell’Avvocato quale conseguenza anche del ridimensionamento delle attribuzioni del Tribunale - 7. Conclusioni.The Attorney’s contribution for the purposes of Processus breviorABSTRACT: This paper concerns the centrality of the attorney in the Processus brevior. Because the Processus brevior’s particular structure compresses the ordinary canonical resources granted by the Legislator to the subjects involved in a matrimonial trial, the attorney becomes its principal director. In particular, the Libellus in a Processus brevior is not a canvas as in the ordinary process but becomes a script binding all parties intending to go ahead with this special canonical instrument until the desired sentence declaring the nullity of marriage.